'Work at the language-face': linguistically innovative poetry in and against the Anthropocene - Carter, Fred (The University of Edinburgh, 2022)
In an essay published in 1979, Wendy Mulford describes linguistically innovative poetics as the rupture of sedimented habits of language-use; ‘to produce meaning across and in defiance of the repressive codes of everyday, communication-ready language,’ she concludes, is to conceive of poetry as ‘work at the “language-face.”’ Situating innovative poetic practice at this intersection of labour, geology, and extraction, Mulford’s evocative phrase insists on ‘the materiality of language,’ its inextricability from histories of fossil capital, and the formal capacity of this excavatory linguistic work as a mode of poetic inquiry. If the Anthropocene articulates an analogous collision of capital, stratigraphy, and historical inscription, I argue that innovative poetry in the late twentieth century offers concrete and resistive forms for thinking through the nonlinear temporalities and scalar discontinuities that have marked this accumulation of crises. Reading linguistically innovative poetry through the environmental humanities, and vice versa, this project situates the British Poetry Revival, Marxist-feminist poetry, and their legacies in contemporary innovative poetics within and against the Anthropocene. Capturing juxtapositions of temporality and scale through lyric, open field, and archival poetic practices, the work of Mulford, Peter Riley, Oli Hazzard, and Callie Gardner reflects the various geologic, energic, oceanic, and metabolic turns that have contoured Anthropocene discourse. While Mulford’s essay figures language as an accumulation of sedimentary deposits, innovative poetics also pushes at the conceptual boundaries of this stratigraphic imaginary through the reconfiguration of poetic forms as energy fields and oceanic archives, compost metabolisms and lyric commons. In doing so, this work brushes the material and conceptual strata of the Anthropocene against the grain; tracing the erasures of slow violence, hidden labour, and counterhegemonic histories that subtend linear narratives of industrial accumulation and catastrophe. Attendant to the relation between the matter of language and the materials of history, linguistically innovative poetry offers a critical juncture for examining intersections between historical materialism and the material turn. Drawing on feminist, environmentalist, and queer Marxisms which both stretch the “materials” of historical materialist inquiry and offer a redress to contemporary tendencies in new materialist thought, this project envisages a reconsideration of the manifold materialisms that cut across the environmental humanities. While recent contributions to the emergent field of Anthropocene poetics have sought to establish innovative poetry as an apparatus through which to grasp the material, scalar, and temporal torsions of climate collapse, the formal difficulties of this work also point continually to the limits of its capacity to articulate the inchoate material relations and nonlinear histories of this emergent epoch. To work at the language-face, as Mulford suggests, is to encounter poetry and history as recalcitrant materials, resistant to extraction, enclosure, or recuperation. Where the Anthropocene frames the geophysical agency of capital as a mode of stratigraphic inscription, linguistically innovative poetry articulates the boundaries of historical legibility through a poetics of failure, absence, and opacity.
Keywords: poetics; Anthropocene; Environmental Humanities; materialism; Marxist-feminism; British Poetry Revival; poetry; Marxist criticism; ecocriticism